Co 2+ /Co + redox tuning in methyltransferases induced by a conformational change at the axial ligand - Kozlowski, Pawel M. (2013)
Density functional theory and quantum mechanics/molecular mechanics computations predict cob(I)alamin (Co+Cbx), a universal B12 intermediate state, to be a pentacoordinated square pyramidal complex, which is different from the most widely accepted viewpoint of its tetracoordinated square planar geometry. The square pyramidality of Co+Cbx is inspired by the fact that a Co+ ion, which has a dominant d8 electronic configuration, forms a distinctive Co+--H interaction because of the availability of appropriately oriented filled d orbitals. This uniquely H-bonded Co+Cbx may have catalytic relevance in the context of thermodynamically uphill Co2+/Co+ reduction that constitutes an essential component in a large variety of methyltransferases.